2015
DOI: 10.1038/onc.2015.89
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNAs as mediators and communicators between cancer cells and the tumor microenvironment

Abstract: Cancer cells grow in an environment comprised of multiple components that support tumor growth and contribute to therapy resistance. Major cell types in the tumor micro-environment are fibroblasts, endothelial cells and infiltrating immune cells all of which communicate with cancer cells. One way that these cell types promote cancer progression is by altering expression of miRNAs, small noncoding RNAs that negatively regulate protein expression, either in the cancer cells or in associated normal cells. Changes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
141
1
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 184 publications
(147 citation statements)
references
References 117 publications
(238 reference statements)
3
141
1
2
Order By: Relevance
“…A large number of miRNAs have been identified in the human genome and each species of miRNA may have multiple mRNA targets [75]. Many individual miRNA species have been shown to play roles in the regulation of stromal cells of the tumor microenvironment and this subject has recently been reviewed [76][77][78][79].…”
Section: Intra-and Intercellular Regulation Of Stromal Cells By Mirnasmentioning
confidence: 99%
See 1 more Smart Citation
“…A large number of miRNAs have been identified in the human genome and each species of miRNA may have multiple mRNA targets [75]. Many individual miRNA species have been shown to play roles in the regulation of stromal cells of the tumor microenvironment and this subject has recently been reviewed [76][77][78][79].…”
Section: Intra-and Intercellular Regulation Of Stromal Cells By Mirnasmentioning
confidence: 99%
“…Thus, elevated miR-21 imparts CAFs with increased MMP2 activity, which contributes to CRC cell invasiveness. Additional examples of miRNAs studied in CAFs are described in Table 2 and reviewed elsewhere [77,78].…”
Section: Intra-and Intercellular Regulation Of Stromal Cells By Mirnasmentioning
confidence: 99%
“…In our previous study, miR-146b-5p was suggested to be an epigenetic signaling molecule that could inhibit NOVA1 [11]. In fact, several studies have shown that stromal cells such as cancer-associated fibroblasts or cancer-associated immune cells are epigenetically regulated within the tumor microenvironment through the microRNA signaling induced by tumor cells [20,21]. The secondarily induced NOVA1 suppression in spindle cells and T cells may result in abnormal tissue matrix function and immune regulation.…”
Section: Discussionmentioning
confidence: 99%
“…Во-вторых, путем паракрин-ной регуляции, в том числе через продукцию в окру-жающую среду ростовых факторов, способных инициировать сигнальные каскады, отвечающие за рост и пролиферацию клеток [16][17][18]. И в-третьих, через продукцию клетками экзосом -мельчайших везикул, содержащих как метаболически активные белки, так и некоторые нуклеиновые кислоты, в том числе микроРНК [19][20][21][22]. Продемонстрировано зна-чение межклеточных взаимодействий в сенсибили-зации опухолевых клеток к цитостатическим препа-ратам, в частности отмечается участие экзосом в развитии и распространении множественной лекар-ственной устойчивости [23,24], изменении клеточ-ной подвижности и миграции [25], однако этот меха-низм практически не исследовался при развитии гормональной резистентности.…”
Section: Introductionunclassified